Flora do Parque Estadual do Ibitipoca, Estado de Minas Gerais, Brasil: Begoniaceae C. Agardh - Delfini Feliciano, Carolina (2018)
A taxonomic survey for Begoniaceae occurring in the Parque Estadual do Ibitipoca (PEIB), Minas Gerais State, Brazil is presented. Eight species of Begonia were found in the Park (B. altamiroi, B. angularis, B. angulata, B. apparicioi, B. cucullata, B. fischeri, B. luxurians and B. rufa), which are distinguished mainly by their general aspect and by the characteristics of leaves, such as, indumentum and blade shape. Of the total of species found, six are restricted to Brazil, whilst fi ve are endemic from the Atlantic Forest. This study was based on a bibliographic review, consult to the main Brazilian herbaria and field observations. Descriptions, illustrations, and comments are also presented for each species. A key to all species is included.